2019
DOI: 10.1111/ijpp.12598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a pharmacist-led intervention on adherence among patients with a first-time prescription for a cardiovascular medicine: a randomized controlled trial in Norwegian pharmacies†

Abstract: Objective To examine whether a pharmacist‐led intervention improves medication adherence among patients who have filled a first‐time prescription for a cardiovascular medicine. Methods Design: Unblinded randomized controlled trial . Setting: 67 Norwegian pharmacies, October 2014–June 2015. Participants: 1480 adults with a first‐time prescription for a cardiovascular medicine. Intervention: Participants in the intervention group received two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…We found that the intervention lowered patients’ concerns about medicines and that patients in the intervention group were more adherent to cholesterol-lowering and aspirin regimens. The combined result of improved medication beliefs and improved adherence behavior has been found in a few other trials [ 53 56 ]. These trials have also tested complex interventions tailored to patients’ individual adherence barriers, but in other patient groups and with other adherence measures.…”
Section: Discussionmentioning
confidence: 72%
“…We found that the intervention lowered patients’ concerns about medicines and that patients in the intervention group were more adherent to cholesterol-lowering and aspirin regimens. The combined result of improved medication beliefs and improved adherence behavior has been found in a few other trials [ 53 56 ]. These trials have also tested complex interventions tailored to patients’ individual adherence barriers, but in other patient groups and with other adherence measures.…”
Section: Discussionmentioning
confidence: 72%
“…The focus of this MAEI is: 1 ) building good habits, 2 ) gaining knowledge and understanding of the prescribed treatment, and 3 ) practical problems and difficulties related to adherence to treatment. The efficacy of this intervention was tested in a randomised controlled trial, and was found effective ( Hovland et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…(26) O profissional farmacêutico, ao realizar suas intervenções em relação à utilização de medicamentos, desempenha papel importante no aumento da adesão de pacientes com doenças cardiovasculares, uma vez que o atendimento desse profissional leva em conta a singularidade do paciente quanto aos sintomas e às crenças sobre sua doença e seu tratamento -importantes causas da não adesão. (27) O uso de polipílulas (termo que abrange formas farmacêuticas sólidas com dose fixa combinada de vários fármacos) foi também estratégia detectada em metanálise com 3.140 pacientes, em seis países, com impacto significativo na adesão, pressão arterial sistólica e lipoproteína de baixa densidade-colesterol (LDL-colesterol) em pacientes com doenças cardiovasculares. (28) As principais barreiras para uso das polipílulas são seu alto custo, tanto para o sistema de saúde quanto para o próprio paciente, a indisponibilidade de várias doses diferentes de um mesmo medicamento que compõem as polipílulas, dificultando o ajuste de dose frequentemente necessário no manejo de doenças cardiovasculares, e o fato de não constarem na relação de medicamentos essenciais.…”
Section: ❚ Resultadosunclassified